2008
DOI: 10.1152/ajpgi.00168.2007
|View full text |Cite
|
Sign up to set email alerts
|

Decreased development of necrotizing enterocolitis in IL-18-deficient mice

Abstract: Necrotizing enterocolitis (NEC) is a devastating gastrointestinal disease predominantly of prematurely born infants, characterized in its severest from by extensive hemorrhagic inflammatory necrosis of the distal ileum and proximal colon. Proinflammatory cytokines have been implicated in the development of NEC, and we have previously shown that IL-18 is significantly elevated in the well-established neonatal rat model of NEC. To determine whether IL-18 contributes to intestinal pathology in NEC, we subjected I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
49
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(51 citation statements)
references
References 45 publications
2
49
0
Order By: Relevance
“…Intestinal inflammation has also been associated with the increase of NF-kappaB, which has been demonstrated to play a key role both in inflammatory bowel disease and gastroschisis (23)(24)(25)(26). We also found elevation of NFkappaB levels both in the intestine and liver of fetuses with gastroschisis (P < 0.05).…”
Section: Discussionsupporting
confidence: 56%
“…Intestinal inflammation has also been associated with the increase of NF-kappaB, which has been demonstrated to play a key role both in inflammatory bowel disease and gastroschisis (23)(24)(25)(26). We also found elevation of NFkappaB levels both in the intestine and liver of fetuses with gastroschisis (P < 0.05).…”
Section: Discussionsupporting
confidence: 56%
“…However, it has been suggested that bacterial endotoxin can trigger an innate immune response characterized by cytokine production (60). Our and other laboratories have shown that proinflammatory cytokines are important factors contributing to NEC pathogenesis (25,27,58). Clinical studies have reported increased serum levels of TNF-␣ and IL-6 in NEC patients (58).…”
Section: Discussionmentioning
confidence: 89%
“…We (26,27) and others (20,41,53) have shown the dysregulation of inflammatory cytokines in the intestinal mucosa during NEC pathogenesis. Par-ticularly, interleukin (IL)-6, IL-8, IL-12, IL-18, and tumor necrosis factor-␣ (TNF-␣) have an important role and a diagnostic value in sepsis and in NEC (9,26,45).…”
mentioning
confidence: 87%